Optimizing Development Through Media Technology of Creativity in the New Normal Era - Tjhin, Santo (Center for Research and Community Service of Sampoerna University, 2022)
Knowledge and technology are an inseparable combination, always developing and giving rise to various new technologies. With the development of technology 4.0 which is very massive and fast, we are forced to be able to live in tandem with the development of digital technology, even in the field of education, the use of digital technology as teaching materials has grown rapidly. The training activities carried out at SDN 01 Caringin have the aim of sharing digital technology knowledge as part of classroom teaching media, to be more effective. By using audiovisual media, internet of things online games makes it easier for students to receive material presented by the SDN 01 Caringin teacher. Seeing the problems and needs of teachers, community service was carried out by holding technology empowerment training. Through this training, it is hoped that teachers can be more creative in utilizing digital technology to the fullest in teaching and be able to develop new teaching patterns in a fun teaching through digital technology.